Influence of foot alignment in anticipatory postural adjustments in children with cerebral palsy - Geraldo, Nathalie (2016)
The difficulty in the organization of anticipatory postural adjustments (APAs) is often associated with lack of postural control (PC) in children/young people with motor spastic hemiplegia, resulting from cerebral palsy (CP). Biomechanical changes of the tibiotarsal and foot characteristics are commonly observed in these children/young people and influence the PC as a whole